What's class got to do with it?. Issue 1 (2nd January 2021) - Walkerdine, Valerie
ABSTRACT: Drawing on my own experience as a working-class academic, as well of that of working-class students in the present, I discuss how the experience for working-class students in elite universities still includes many aspects of classism, even when those students can, and do, do very well indeed and even when policies are apparently in place to support them. With class not being a protected characteristic in the 2010 UK Equality Act, issues of classism tend to be ignored and relegated to the Widening Participation agenda, where serious issues of classism, tend to be ignored. The paper discusses how this the eliding and effacing of class has arisen and what needs to be done to confront it, including the central role of working class academics in the critique of logocentrism and the possibility of a new work towards an ecology of classed relations. The paper asks how a different understanding of class as currently lived might help advance an agenda for the study of class in higher education today and in the future.